WRITERS CRITICIZED BY JACK LONDON (American Journal of Interdisciplinary Research and Development, 2024)
Jack London, a prominent American author, was known not only for his literary contributions but also for his candid critiques of other writers. In his essays and letters, London expressed sharp opinions about various authors of his time, often highlighting what he perceived as shortcomings in their work. This abstract delves into London's criticisms of fellow writers, examining his views on their styles, themes, and overall literary merit. By analyzing London's critiques, we gain insights into his own literary preferences and the broader literary landscape of the early 20th century. This study seeks to understand the impact of London's criticisms on the writers in question and their reception within the literary community. Through this lens, we explore how London's views contributed to the ongoing discourse on literature and artistic expression during his era.